Risk factors for major adverse cardiovascular events after coronary artery bypass grafting using radial artery grafts - Xia, Tianyu; Li, Bo; Zhang, Wei; Wang, Zhe; Ye, Xiaofeng; Zhou, Mi; Li, Haiqing; Qiu, Jiapei; Zhu, Yunpeng; Zhao, Qiang (Frontiers in Cardiovascular Medicine, 2023)
Background: Coronary artery bypass grafting using radial artery grafts (RA-CABG) improved the long-term outcomes. However, major adverse cardiovascular events (MACEMACE-4, including allcause death, myocardial infarction, stroke and repeat revascularization) after RA-CABG still occurred and the predictors remain uncertain. This study aimed to detect independent risk factors of MACEMACE-4 after RA-CABG. Methods: Retrospective case-control study (NCT04935086) was conducted among patients underwent primary isolated RA-CABG between 2009 and 2019 in our center. Baseline characteristics, procedure characteristics and medication use, were compared to identify the independent predictors of MACEMACE-4, all-cause death and myocardial infarction (MI) with univariate and then multivariate logistic regression.Results: A total of 370 patients (96.1%) were analyzed with available follow-up data of mean 48.8±41.0 months. MACEMACE-4, all-cause death and MI occurred in 102 patients (27.6%), 27 (7.3%) and 66 patients (17.8%), respectively. Multivariate analysis revealed prior MI (OR=2.12, 95%CI 1.05-4.25, P=0.04) and RA to left anterior descending artery (LAD) (non-left internal mammary artery to LAD) (OR=4.87, 95%CI 1.41-16.82, P=0.01) as independent predictors of MACEMACE-4 after surgery. Female (OR=4.53, 95%CI 1.06-19.41, P=0.04), left ventricular ejection fraction (LVEF) <40% (OR=21.00, 95%CI 1. P=0.04) and RA to LAD (OR=8.55, P=0.02) were independent predictors of all-cause death. Prior MI (OR=3.11, P=0.006) emerged as an independent predictor of MI. Field Code Changed 2 This is a provisional file, not the final typeset article Conclusion: Our data suggested that prior MI and RA to LAD were independent predictors of MACEMACE-4 after RA-CABG. While female, LVEF<40% and RA to LAD indicated death. Prior MI indicated new MI.